Teunomyces basidiocarpi sp. nov. and Teunomyces luguensis sp. nov., two ascomycetous yeast species related to the Candida kruisii clade isolated in Taiwan. Issue 3 (29th January 2020) - Chang, Chin-Feng; Liu, Yi-Ru; Lee, Ching-Fu
Abstract : Four strains of anamorphic yeasts isolated from the fruiting bodies of mushrooms collected in Taiwan were found to represent two novel yeast species belonging to the genus Teunomyces, which was formally known as the Candida kruisii clade. Strains NY13M09 T and NY14M14 were related to the type strains of Teunomyces panamensis, T. pallodes, T. tritomae and T. lycoperdinae, and strains GG4M07 T and GG6M14 were related to T. kruisii NRRL Y-17087 T and T. cretensis NRRL Y-27777 T . However, strains NY13M09 T and NY14M14 differed from their closest phylogenetic neighbours by 2.9–3.7 % in the D1/D2 domain sequence of the LSU rRNA gene and by 6.6–13.7 % in the internal transcribed spacer (ITS); GG4M07 T and GG6M14 differed from their closest known species by 2.4 % in the D1/D2 domain sequence of the LSU rRNA gene and by 8.7–10.0 % in the ITS. Meanwhile, these strains were also clearly distinguished from their closest relatives based on the results of physiological tests. Based on the characteristics described above, the strains could be regarded as representing two novel species of the genus Teunomyces, for which the names Teunomyces basidiocarpi sp. nov. and Teunomyces luguensis sp. nov. are proposed. The holotypes are Teunomyces basidiocarpi BCRC 23475 T and Teunomyces luguensis BCRC 23476 T .